1992
DOI: 10.1021/ja00047a043
|View full text |Cite
|
Sign up to set email alerts
|

The effect of basis set and electron correlation on the predicted electrostatic interactions of peptides

Abstract: The realism of molecular modelling studies of peptides depends on the model of the electrostatic forces, and thus on the quality of the wave function used to derive the atomic charges or multipoles. To establish this dependence, we have studied the electrostatic properties of N-acetylalanine Wmethylamide (CH3CONHCHCH3CONHCH3) calculated from a distributed multipole representation of both SCF and correlated wave functions with a range of respectable basis sets. The electron correlation is included in the wave f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 0 publications
5
31
0
Order By: Relevance
“…See the appendix in ref. 13 dicted to be 22.560 kcal/mol above the planar conformation and is not along the reaction coordinate.…”
Section: Molecular and Atomic Energeticsmentioning
confidence: 98%
“…See the appendix in ref. 13 dicted to be 22.560 kcal/mol above the planar conformation and is not along the reaction coordinate.…”
Section: Molecular and Atomic Energeticsmentioning
confidence: 98%
“…13 All of the above theoretical calculations were done using the basis set 6-3IG** (split-valence plus d-type and p-type polarization functions). 14 It has been previously shown 1516 that the neglect of electron correlation in self-consistent wave functions results in an overestimation of the electrostatic interactions and that this overestimate is mainly a scaling effect A scaling factor of 0.9 was shown to give improved agreement between the calculated and the experimental dipole moments for a set of eight small molecules, 15 in a study of the electrostatic interactions of a dipeptide, 16 and in determining the crystal structures of polar organic molecules. 17 Our previous study of the nitramine crystals 4 showed that the use of the 0.9 scaling factor for the electrostatic charges determined at the HF level significantly improves the accuracy of the predicted lattice energies of the crystals.…”
Section: Il Intermolecular Potentialmentioning
confidence: 99%
“…Cox and Williams [25] have suggested that a scaling factor of 0.9 can be used to improve agreement between the calculated and experimental values of the dipole moments for a set of eight small molecules. The same factor has been justified in a study of the electrostatic interactions of a dipeptide [26], as well as in a more recent work related to the role of electrostatic interactions in determining the crystal structures of polar organic molecules [10].…”
Section: Intermolecular Potentialmentioning
confidence: 89%
“…It has been shown previously [25,26] that the neglect of electron correlation in self-consistent wave functions overestimates the electrostatic interactions; however, this is mainly a scaling effect. Cox and Williams [25] have suggested that a scaling factor of 0.9 can be used to improve agreement between the calculated and experimental values of the dipole moments for a set of eight small molecules.…”
Section: Intermolecular Potentialmentioning
confidence: 93%